Optimalisasi Pemanfaatan Aplikasi Google Classroom Dan Google Form Sebagai Penunjang Pembelajaran Daring Di SMA Negeri 5 Cimahi - Hidayat, Hidayat; Wicaksono, M Fajar; Rahmatya, Myrna D; Lubis, Riani; Nurhayati, Sri (Indonesian Community Service and Empowerment Journal (IComSE), 2020)
ABSTRACT The purpose of community service activities with the theme of using Google Classroom and Google Form for SMAN 5 Cimahi teachers is to provide training to teachers of SMAN 5 Cimahi in order to optimize the use of the Google Classroom and Google Form applications in online learning carried out during the Covid-19 pandemic conditions. The method used in this activity is a description of the features of Google Classroom and Google Form. In Google Classroom, it explains about opening classes, inviting participants or students, creating student attendance, uploading material and using the reuse feature, processing grades and downloading assessment results in the form of a spreadsheet. In Google Form, it explains how to set the Form as a Quiz, inserts picture or equation questions, inserts questions from Google Docs and creates Form links that have been created. Next, do a demonstration of using the application. Both activities were carried out online through the Zoom application media. The next step, each teacher was assigned to operate the two applications according to the directions in the training. The results of the activity showed that the teachers gained additional knowledge in operating those applications. Key words: google classroom, google form, class attendance, online learning, reuse feature. ABSTRAK Tujuan kegiatan pengabdian pada masyarakat dengan tema pemanfaatan Google Classroom dan Google Form bagi guru SMAN 5 Cimahi adalah untuk memberikan pelatihan kepada para guru SMAN 5 Cimahi agar dapat mengoptimalkan penggunaan aplikasi Google Classroom dan Google Form dalam pembelajaran daring yang dilakukan selama kondisi pandemik Covid-19. Metode yang digunakan dalam kegiatan ini adalah pemaparan mengenai fitur-fitur pada Google Classroom dan Google Form. Pada Google Classroom dipaparkan tentang membuka kelas, mengundang peserta atau siswa, membuat presensi siswa, mengunggah materi dan menggunakan fitur reuse, mengolah nilai dan mengunduh hasil penilaian dalam bentuk spreadsheet. Pada Google Form dipaparkan tentang bagaimana mengatur Form sebagai Quiz, menyisipkan soal gambar atau persamaan, menyisipkan soal dari Google Docs dan membuat tautan Form yang telah dibuat. Selanjutnya, melakukan demonstrasi penggunaan aplikasi tersebut. Kedua kegiatan tersebut dilakukan secara daring melalui media aplikasi Zoom. Langkah berikutnya setiap guru ditugaskan untuk mengoperasikan kedua aplikasi tersebut sesuai arahan dalam pelatihan. Hasil kegiatan menunjukkan bahwa para guru memperoleh penambahan pengetahuan dalam mengoperasikan kedua aplikasi tersebut. Kata kunci: google classroom, google form, presensi siswa, pembelajaran daring, fitur reuse.